Endovascular treatment of intracranial internal carotid artery bifurcation region aneurysms - Xu Liu; Yunbao Guo; Kun Zhang; Jinlu Yu (Frontiers in Neurology, 2024)
Intracranial internal carotid artery (ICA) bifurcation region aneurysms are uncommon. When treatment is necessary for ICA, endovascular treatment (EVT) can be a useful option. Due to the complexity of these aneurysms and the variability of EVT techniques, EVT for ICA bifurcation aneurysms is challenging. Currently, it is necessary to perform a review to explore this issue further. In this review, the following issues were discussed: the anatomy of the ICA bifurcation region; the classification, natural history and EVT status of ICA bifurcation region aneurysms; the technique used for identifying ICA bifurcation region aneurysms; and the prognosis and complications of EVT for ICA bifurcation region aneurysms. According to the review and our experience, traditional coiling is currently the preferred therapy for ICA bifurcation region aneurysms. In addition, in select cases, new devices, such as flow diverters and Woven EndoBridge devices, can also be used to treat ICA bifurcation region aneurysms. Generally, EVT is an alternative treatment option for ICA bifurcation region aneurysms.